PENGELOLAAN TBM CAKRAWALA DALAM MENGOPTIMALKAN PROGRAM WAJIB BACA BAGI WARGA BELAJAR KEJAR PAKET B - Meily Waniqmah; Muarifuddin Muarifuddin (Jurnal Manajemen Pendidikan, 2026)
The implementation of the compulsory reading program at the Cakrawala Kindergarten is still limited in terms of duration and variety of activities, making it less than optimal in increasing the interest and participation of Package B learners. This study aims to describe the role of Cakrawala Kindergarten managers in optimizing the compulsory reading program for Package B learners, analyzing management strategies, and identifying supporting and inhibiting factors in program implementation. This study uses a descriptive qualitative approach with research subjects being managers and Package B learners. Data collection techniques through interviews, observation, and documentation. The results show that managers carry out managerial functions including planning, organizing, implementing, and evaluating. The strategies implemented include providing motivation and appreciation, creating an interesting learning atmosphere, selecting reading materials according to interests, and literacy innovations such as media conversion. Supporting factors include the availability of facilities, book collections and manager support, while inhibiting factors include limited time and low initial reading interest. The novelty of this study lies in the focus of the study which emphasizes the role of TBM managers in optimizing the compulsory reading program on the Package B equivalency education pathway.